DESIGN OF COMIC BOOKS AS A MEDIA TO INTRODUCE CLEAN BEHAVIOR AND PROTECTING THE ENVIRONMENT FOR ELEMENTARY STUDENTS - Zulmi, Muhammad; Sugiarto, Eko (Jurusan Seni Rupa Fakultas Bahasa dan Seni, 2022)
Many of the damaged environment and pollution that occurs as well as the spread of disease is manmade. One of the factors is the bad habits of people who are not aware of the importance of maintaining cleanliness and the environment. Providing awareness about the importance of clean behavior and protecting the environment should be done from an early age to be more effective. Therefore, the purpose of this study project is to design a media to introduce clean behavior and protect the environment for children that is interesting and fun, namely through the medium of comics. The reason for choosing comics is expected to be able to overcome problems in understanding a material. The use of analogies and depictions of stories in life can help students to understand a material. In designing this comic book the author uses two techniques, traditional and digital. There are several stages in the design, the pre-production process including idea search, literature study, and analysis, then the production process including script and storyboard design, sketching, inking, scanning, and editing, and the last post-production is publication or exhibition. This design resulted in a comic book entitled